(3QSGdI aj QDjI THM GdTF aj GdeGAs - (3GejQ MSjf s ((3eMeO Hf CHj HcQ GdKfGI TjQS s)
(3ChdgG (B:s
(3Ydi Gddg CJhcd aQLYJ Edi GdgfOSI dOaY GdhShSI hCUHJ HQGgjf s
(3BNQgG (B:s
(3hEfeG CWfHJ GdcdGe ai gPG GdeQGe hGdJhcd Ydi NGdb GdCQV hGdSehGJ GdSHY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1/1918) s
Keywords: (3Gdadcs